Water Scenes in American Renaissance Literature: Poe’s Maelström and Thoreau’s Pond - Della Marca, Manlio (Oltreoceano - Rivista sulle migrazioni, 2024)
Water Scenes in American Renaissance Literature: Poe’s Maelström and Thoreau’s Pond From the seas and oceans in the short stories and novels by Herman Melville and Edgar Allan Poe through Henry David Thoreau’s description of the pond in Walden, to Mark Twain’s Mississippi, there is hardly any American “classic” in which water does not play an important function as both central symbol and key element of the narrative. This essay dives into this rich tradition by examining some compelling water scenes in Poe’s “A Descent into the Maelström” (1841) and Thoreau’s Walden (1854). More specifically, in the first part, I suggest that the whirlpools and vortexes in Poe’s sea stories allegorize the disorienting situation in which the modern subject finds itself. In order to capture this specific dimension of Poe’s writing, I invoke here Zygmunt Bauman’s notion of “liquid modernity”, though I put a slightly different spin on it. I also look at how such key twentieth-century thinkers as Gaston Bachelard, Theodor W. Adorno, and Marshall McLuhan responded to Poe’s use of water and vortical imagery. In the second part of the essay, I turn to Thoreau’s Walden, and I discuss how “semantic overturning” is one of the rhetorical strategies underlying the use of water symbolism in this foundational text of the American Renaissance.